Cation Charge and Size Selectivity of the C2 Domain of Cytosolic Phospholipase A(2) - Nalefski, Eric A. (2002)
C2 domains regulate numerous eukaryotic signaling proteins by docking to target membranes upon binding Ca(2+). Effective activation of the C2 domain by intracellular Ca(2+) signals requires high Ca(2+) selectivity to exclude the prevalent physiological metal ions K(+), Na(+), and Mg(2+). The cooperative binding of two Ca(2+) ions to the C2 domain of cytosolic phospholipase A(2) (cPLA(2)-α) induces docking to phosphatidylcholine (PC) membranes. The ionic charge and size selectivities of this C2 domain were probed with representative mono-, di-, and trivalent spherical metal cations. Physiological concentrations of monovalent cations and Mg(2+) failed to bind to the domain and to induce docking to PC membranes. Superphysiological concentrations of Mg(2+) did bind but still failed to induce membrane docking. In contrast, Ca(2+), Sr(2+), and Ba(2+) bound to the domain in the low micromolar range, induced electrophoretic mobility shifts in native polyacrylamide gels, stabilized the domain against thermal denaturation, and induced docking to PC membranes. In the absence of membranes, the degree of apparent positive cooperativity in binding of Ca(2+), Sr(2+), and Ba(2+) decreased with increasing cation size, suggesting that the C2 domain binds two Ca(2+) or Sr(2+) ions, but only one Ba(2+) ion. These stoichiometries were correlated with the abilities of the ions to drive membrane docking, such that micromolar concentrations of Ca(2+) and Sr(2+) triggered docking while even millimolar concentrations of Ba(2+) yielded poor docking efficiency. The simplest explanation is that two bound divalent cations are required for stable membrane association. The physiological Ca(2+) ion triggered membrane docking at 20-fold lower concentrations than Sr(2+), due to both the higher Ca(2+) affinity of the free domain and the higher affinity of the Ca(2+)-loaded domain for membranes. Kinetic studies indicated that Ca(2+) ions bound to the free domain are retained at least 5-fold longer than Sr(2+) ions. Moreover, the Ca(2+)-loaded domain remained bound to membranes 2-fold longer than the Sr(2+)- loaded domain. For both Ca(2+) and Sr(2+), the two bound metal ions dissociate from the protein–membrane complex in two kinetically resolvable steps. Finally, representative trivalent lanthanide ions bound to the domain with high affinity and positive cooperativity, and induced docking to PC membranes. Overall, the results demonstrate that both cation charge and size constraints contribute to the high Ca(2+) selectivity of the C2 domain and suggest that formation of a cPLA(2)-α C2 domain–membrane complex requires two bound multivalent metal ions. These features are proposed to stem from the unique structural features of the metal ion-binding site in the C2 domain.